PUTTING IDEAS BACK IN PLACE? non-linear temporalities in Brazil’s authoritarian neoliberalism and its digital infrastructure - Cesarino, Letícia (Universidade Federal da Bahia, 2021)
The article approaches how the populistauthoritarian inflection of global neoliberalism has gained traction in Brazil through friction withits post-colonial historical condition, marked by a disjunction between egalitarian, universalist liberal ideals and an unequal, particularistic socialreality. I will pay special attention to infrastructural convergences between neoliberalization and platformization, which, by creating a paradoxicaltemporality of permanent crisis, resonate with “forces and powers” that also operate non-linearlyaccording to a metaphysics of disorder, such as the various forms of nostalgia, millenarianism, andtraditionalism that follow the rise of the radical right throughout the world. I developed this argument focusing on two moments of Bolsonarism: the populist messianism during the 2018 elections, and its paradoxical routinization as a parasitic government operating in a temporality of exception, during the Covid-19 pandemic. This article suggestes that, in the face of the illiberal drift ofcontemporary neoliberalism, Bolsonarism propels Brazil into an avant-garde, putting ideas “back inplace”.